KIRKPATRICK EVALUATION MODEL IN OPERATIONAL CURRICULUM DEVELOPMENT TRAINING FOR EDUCATIONAL UNITS EARLY CHILDHOOD LEVEL IN SOUTH TANGERANG CITY - Handayani, Nungki Sri; Pramono, Rudy (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
In an effort to implement the change of the independent curriculum, each school is required to prepare an Operational Curriculum of the Education Unit (KOSP) document as a guideline for implementing the curriculum, but many do not understand the implementation of KOSP in the independent curriculum, this also happened in the PAUD education unit in South Tangerang City so that KOSP training was carried out. The purpose of this study was to analyze the results of the KOSP training using the Kirkpatrick evaluation model. This study uses a mixed method, data obtained from questionnaires, observations and interviews were processed using qualitative and quantitative approaches. Qualitative data are described narratively while quantitative data are processed with validity, reliability and T-test tests. The results of this study found that the KOSP evaluation uses 4 stages, namely the reaction stage, learning stage, behavior stage and impact stage. The reactions of training participants to the organizers and speakers gave positive reactions from "Satisfactory" to the qualification "Very Satisfactory". At the learning stage, all participants graduated with an average qualification of "Quite Satisfactory". At the behavioral stage, participants based on the perceptions of superiors, colleagues and students obtained the qualification "Very Satisfactory". At the stage of the training impact on participants, evaluation results were also obtained with the qualification "Very Satisfactory". So based on the findings, it was concluded that the KOSP training in terms of process and results was declared effective and efficient in improving teacher competence related to the preparation of KOSP documents.